Potentiometric field-effect transistor pH sensing in a low-power wide-area network - Akmal Mustaffa Zulhakim; Wan Fazlida Hanim Abdullah; Ahmad Zaki Abu Bakar; Robaiah Mamat; Ili Shairah Abdul Halim; Muhammad Izzat Alif Muslan; Sukreen Hana Herman (Institute of Advanced Engineering and Science, 2024)
This research paper explores the application of extended-gate field-effect transistors (EGFET) as a potentiometric sensing method for pH detection within an internet of things (IoT) system. The pH EGFET sensor is integrated with a long-range (LoRa) microcontroller, enabling data transmission via a low-power, long-range wide-area network (LoRaWAN) IoT framework to a dedicated IoT application server. The framework utilizes a message queuing telemetry transport (MQTT) broker, employing a publish/subscribe message architecture for efficient data transmission. The study focuses on addressing the problem of determining whether EGFET technology can provide precise and dependable measurements in various settings. To achieve this, the data from the IoT framework is compared with data signals from a semiconductor parametric analyzer and a readout interfacing circuit serial data acquisition (DAQ). From the study, EGFET sensors provide a sensitivity of 61.1 mV/pH with a linearity of 0.9968 through the IoT method. Meanwhile, non-IoT methods yield slightly different sensitivities of 53.1 and 50.5 mV/pH with comparable linearity of 0.9984 and 0.9979. Overall, the research demonstrates the versatility of EGFET technology, highlighting its effective use in various sensing instruments, while ensuring reliable data transfer through the LoRaWAN framework.